Julian Bond's time to teach : a history of the southern civil rights movement - Bond, Julian, 1940-2015 (Beacon Press, 2021)
"Compiled from his original lecture notes, Julian Bond's Time to Teach brings his invaluable teachings to a new generation of readers and provides a necessary toolkit for today's activists in the era of Black Lives Matter."--